Preface - Gao, Y.; Xu, Z.; Wang, Lei; Xu, Honglei (American Institute of Mathematical Sciences, 2015)
This Special Issue of Numerical Algebra, Control and Optimization (NACO) is dedicated to Professor Enmin Feng for his important contributions in Applied Optimization, Optimal Control, System Identification and Large Scale Computing and their Engineering Applications and on the occasion of his 75th Birthday.